Application of a Multi-Criteria Decision Support Tool in Assessing the Feasibility of Implementing Treated Wastewater Reuse - Adewumi, J.R; Ilemobade, A.A; van Zyl, J.E (International journal of decision support system technology, 2013)
Wastewater reuse is increasingly becoming an important component of water resources management in many countries. Planning of a sustainable wastewater reuse project involves multi-criteria that incorporate technical, economic, environmental and social attributes. These attributes of sustainability is the framework upon which the decision support tool presented in this paper is developed. The developed tool employs a user friendly environment that guides the decision makers in assessing the feasibility of implementing wastewater reuse. The input data into the tool are easily obtainable while the output is comprehensive enough for a feasibility assessment of treated wastewater reuse. The output is expressed in terms of effluent quality, costs, quantitative treatment scores and perception evaluation. Testing of the developed multi-criteria decision support tool using Parow wastewater treatment works in Cape Town showed the tool to be versatile and capable of providing a good assessment of both qualitative and quantitative criteria in the selection of treatment trains to meet various non-potable reuses. The perception module provided a quick assessment of potential user’s concerns on reuse and service providers’ capacity.